Data Warehouse Analysis to Support UMKM Decisions using the Nine-step Kimball Method - Wira Darma, I Gede; Sri Utami, Komang; Sri Aryani, Ni Wayan (International Journal of Engineering and Emerging Technology; Vol 4 No 1 (2019): January - June, 2019)
Micro, small and medium enterprises are one of the drivers of the economy. In the current technological era, companies have supported information systems to process business transactions. Naris Mart is one of the MSMEs engaged in retail with a business that has been running for 6 years. During the span of 6 years, of course, many buying and selling transactions were carried out. To help analyze how the business work, will be designed a data warehouse. Data warehouses need to be made so that they can receive information, reports, and can carry out multi-dimensional analysis that can ultimately help business owners. The design of the data warehouse uses the Nine-step Kimball methodology. Results obtained in the form of star schema and retail data warehouse analysis. The data warehouse can provide fast, accurate and continuous information that can help management in making policies for the future to come. In general, the benefit of this research is that additional references in building a data warehouse use the Nine-step Kimball methodology